Diseños industriales e inteligencia artificial. - Cocha Chicaiza Danilo Josue (2025)
The relationship between industrial designs protected by industrial property and artificial intelligence (AI) has become a crucial issue in the legal and technological field, especially in a context where innovation and automation are constantly growing. Historically, the protection of industrial designs has focused on novelty and human creation, elements that have traditionally been clear in the regulatory framework. However, the advancement of AI has introduced a series of challenges that force us to reexamine these issues. AI has the ability to autonomously create designs through machine learning algorithms and neural networks. This phenomenon raises questions in this relationship. Investigating this relationship is not only relevant from a legal perspective, but also crucial for promoting an innovation environment that is fair and equitable in the field of industrial property. This synergy can pave the way to a future where human creativity and technological automation coexist harmoniously. Ecuador is no exception; artificial intelligence has entered the intellectual property dynamics of society, which include the creative and legal aspects, without yet a positive national response For the development of the study, a theoretical legal research with a qualitative approach has been chosen and methodologically, methods from the classic Social Sciences have been combined with methods from the Legal Sciences. In this sense: analysis-synthesis, logical-legal, exegetical, comparative law and hermeneutic. Regarding the techniques, the bibliographic review is chosen. Based on this, the aim is to obtain as results, a study that analyzes the theoretical and regulatory foundations on industrial designs and artificial intelligence and its implications in the Industrial Property Law of the Republic of Ecuador, based on its 5 international expression and in the Law. compared to Latin America (Argentina, Panama and Peru) Keywords: Industrial designs, artificial intelligence, industrial property